Pelatihan Soft Skill Komunikasi untuk Meningkatkan Peluang Kerja Mahasiswa sebagai Calon Tenaga Kerja Baru - Nengsi, Ayu Rahma; Didi Sartika (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) IAIN Lhokseumawe, 2022)
The purpose of this community service activity is to provide soft skills training in improving the ability to communicate effectively to prospective tertiary graduates. This is motivated by the lack of student communication skills, especially effective speaking communication. This mixed method research was carried out by describing the dominant qualitative data and then the data was complemented by quantitative data obtained from the survey. Qualitative data collection techniques were carried out by means of participant observation, interviews, document studies. The results showed that the main target of the training were students of the Faculty of Sharia and Tarbiyah IAIN Takengon as training participants totaling 40 people. Regarding the soft kill training method, it is carried out in 4 steps, namely: 1) prologue of training activities, 2) learning, 3) discussion and question and answer, 4) evaluation of activity results. The training process was carried out in 10 meetings, with 2 different sessions, namely listening and speaking communication skills improvement sessions. The results of the evaluation of the communication skills training activities showed that there was a significant increase in the abilities experienced by the participants. This can be seen from the data, that there was a very good increase of up to 90% of the total participants in listening communication skills. As for speaking communication skills, it was also seen that there was an increase from all participants reaching more than 50% of the total participants experiencing very good progress in improving speaking communication skills. Speaking communication skills are a bit difficult to improve. This is influenced by several factors, including aspects of courage and self-confidence of the participants that still need to be improved. Courage and low self-confidence make them shy in conveying the ideas they have in mind.